A study on relationship between service quality and customer loyalty: A case study of Melaka International Trade Centre (MITC) / Farhana Yusoff - Yusoff, Farhana (Faculty of Business and Management, 2007)
There are so many competitors in the industry especially from the service industry. In this regard, MITC has a crucial and challenging task in monitoring as well as measuring customer satisfaction and loyalty towards its service quality. Therefore, the objectives of this study are to ascertain the customers' level of perception and loyalty towards MITC service quality and to determine the relationship between the two variables. The researcher has used service quality to measure the customers' perception towards MITC's service performance. There are five dimensions under service quality included tangible, reliability, responsiveness, assurance, and empathy. Beside that, to measure the loyalty, the researcher focuses on repurchase intention and recommending to others. Furthermore, the populations for this research are the customers of MITC which totaled 384. The target population is customers that have used MITC's service in Melaka from Jan 2003- Dec 2006. The sample size of this study is 50 respondents. The study involves a descriptive research in order to describe the characteristics of variables chosen. Moreover, the probability sampling has been chosen by the research to conduct this study. The statistical techniques that were used to analyze the data are reliability test, frequency distribution, and Pearson correlation coefficient. From the findings, it can be concluded that MITC's performance is good and most of their customers are satisfied, happy and loyal towards MITC's service quality. Therefore, it is clearly seen that service quality has a direct relationship with loyalty.